Switchable Quarter-Wave Plate and Half-Wave Plate Based on Phase-Change Metasurface - Yaru Li; Jun Luo; Xiong Li; Mingbo Pu; Xiaoliang Ma; Xin Xie; Jianping Shi; Xiangang Luo (IEEE Photonics Journal)
Wave plates as important polarization control devices are widely used in the applications of biomedical imaging, fiber optical communication, astronomy, semiconductor industry and aerospace etc. To make the wave plate actively tunable, we propose a rectangular antenna-based metasurface based on the phase-changing material Ge2Sb2Te5 (GST) with high transmittance and polarization conversion rate. Before the GST phase transition, the metasurface operates as a quarter-wave plate in the wavelength range of 10.0–11.9 μm. After the GST turning into crystalline state, the metasurface operates as a half-wave plate in the wavelength range of 10.3–10.9 μm. The physical mechanism for the high transmittance efficiency and polarization conversion rate attributes to the combination of the electric dipole and magnetic dipole resonances. Moreover, the adjustable wavelength range can be further extended by changing the geometry of antenna-based GST to selectively enhancing or suppressing the electric and magnetic resonances. This work provides a new strategy for tunable wave plate, which would have the potential in the application of multi-functional integrated optical systems.